The absent-minded imperialists : empire, society, and culture in Britain - Porter, Bernard (ACLS Humanities E-Book., 2004)
Kipling, Elgar, Mafeking Night ... all these conjure up an image of a British society besotted with imperial pride in the nineteenth and early twentieth centuries. In fact the true picture was more complex than this and people reacted to their empire in different ways. Many were hardly aware of it at all. This lively book is the first study of the impact of the empire on British society and culture that looks beneath the surface to find out what people really thought, with some. surprising results. - ;The British empire was a huge enterprise. To foreigners it more or less defined Britain in.